2014
DOI: 10.2478/bj-2014-0019
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Salivary Changes in Patients with Chronic Kidney Disease

Abstract: Introduction. Kidney disease is associated with many abnormalities in the oral health status as well as with alterations in salivary flow and composition. The aim of this study was to evaluate and to correlate oral clinical findings, salivary flow (SF) and salivary pH values in patients with chronic kidney disease (CKD) not yet on hemodyalisis treatment, those undergoing hemodialysis and in kidney transplant recipients. Methods. In a cross-sectional study 90 patients were included. The cohort was composed of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
8
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
7
8
2
Order By: Relevance
“…Of the patients in our study, 10.8% suffered from oral candidiasis (2% pseudomembranous, 8% erythematous, and 0.8% hyperplastic), and no angular cheilitis was observed. This rate was almost similar to the results of studies by Oyetola et al, Belazelkovska et al, Gavaldac C et al and Gautam NR et al (9,22,24,25) Our results differed from the results reported by de la Rosa García et al and Ruospo M, et al (7,26) This difference can be due to different nutrition and different health conditions in these patients.…”
Section: Resultsupporting
confidence: 91%
See 2 more Smart Citations
“…Of the patients in our study, 10.8% suffered from oral candidiasis (2% pseudomembranous, 8% erythematous, and 0.8% hyperplastic), and no angular cheilitis was observed. This rate was almost similar to the results of studies by Oyetola et al, Belazelkovska et al, Gavaldac C et al and Gautam NR et al (9,22,24,25) Our results differed from the results reported by de la Rosa García et al and Ruospo M, et al (7,26) This difference can be due to different nutrition and different health conditions in these patients.…”
Section: Resultsupporting
confidence: 91%
“…(21) Belazelkovska et al, in their study on 30 dialysis patients and 30 renal transplantation patients, reported that 72.22% of the patients showed oral manifestations. (22) The results of these three studies differed from those of our research, which may be due to the studied population, nutritional habits, and the region under study.…”
Section: Resultcontrasting
confidence: 81%
See 1 more Smart Citation
“…Our results also showed that salivary flow rate significantly decreases as the stage of CKD increased. The results in the present study are in accordance with previous studies of Bayraktar et al 20,22 and Belazelkovska et al 26 This study has certain limitations. A cross-sectional design and convenience sample in the hospital were used thus it is difficult to draw cause and effect conclusions.…”
Section: Discussionsupporting
confidence: 91%
“…Given the chronic uremic state, several alterations frequently occur in the oral cavity among them: uremic stomatitis, gingival hyperplasia, enamel hypoplasia, petechiae and ecchymosis, gingival bleeding, halitosis, increased tartar formation, dental erosion, hyposalivation, xerostomia, angular cheilitis, dysgeusia, and increased incidence of dental caries . These oral alterations can negatively influence the quality of life of patients on hemodialysis treatment …”
Section: Introductionmentioning
confidence: 99%